Eksekusi Putusan Verstek Terhadap Pemenuhan Hak Istri Dan Anak Dalam Perkara Gugat Cerai - Anik Tri Haryani; Sigit Sapto Nugroho; Nindichya Imtiyyas Pusparini; Retno Iswati (Universitas Merdeka Madiun, 2024)
Abstract – The aim of this research is to find out how the verstek decision is imposed on the defendant in a divorce case and to find out how the execution of the verstek decision affects the fulfillment of the rights of his wife and children in a divorce case. The method applied in this research is normative juridical through statutory and conceptual approaches. With primary and secondary sources of legal materials used. The results of this research are regarding the responsibility of the husband (defendant) for meeting the needs of his wife and children due to the verstek decision. The judge will give a verstek decision if a defendant does not come to court at all. The judge will give a penalty to the defendant regarding the claim for payment of maintenance, by adding